Epoxy resin adhesive as well as preparation method and application thereof
By combining barium titanate and emelanin in epoxy resin adhesive, and using silane coupling agent surface modification and tannin to form reversible hydrogen bonds based on photothermal conversion, the problems of adhesive reuse and waste of resources are solved. It achieves efficient adhesive reuse and environmental protection effects.
Patent Information
- Application Number
- CN202311515564.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2024-12-13
AI Technical Summary
The existing adhesives are difficult to reuse after use, and traditional desorption methods consume resources, and the accumulation of eumelin in the polymer leads to a reduced electron transport capability, and the lack of reversible adhesives based on the photothermal conversion effect.
Using epoxy resin adhesive, barium titanate is modified by combining barium titanate and emelanin, and silane coupling agent surface is added, tannin and 4,4-diaminobiphenyl are added to form a reversible hydrogen bond based on photothermal conversion. and ester bonds to achieve reusing adhesives.
The high dielectric constant and photothermal conversion of the adhesive are achieved, the insulation and adhesion ability are enhanced, multiple cycles are supported, and the production cost and energy consumption are reduced.
Smart Images

Figure CN119119929A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to an epoxy resin adhesive and a preparation method and application thereof. Background Art
[0002] In modern adhesive technology, traditional commercial adhesives have a series of problems such as poor recyclability and low spatial resolution during the bonding process. Moreover, in the process of debonding the adhesive and the adhesive, high-temperature cooking or strong acid or alkali soaking and other desorption methods are generally required, resulting in a waste of resources. Compared with traditional adhesives, reversible adhesives are recyclable and have a positive role in promoting environmental protection and resource conservation. At present, the method of realizing reversible adhesives is mainly achieved by introducing a combination of non-covalent bonds and reversible covalent bonds. Covalent bonds include van der Waals forces, hydrogen bonds, and charge effects. Reversible covalent bonds include Diels-Alder reactions, disulfide bonds, dynamic borate bonds, etc. However, there is currently no method to achieve the reversibility of adhesives based on the photothermal conversion effect.
[0003] Eumelanin is a natural melanin extracted from the ink sac of cuttlefish. It has multiple functions, including photoprotection, anti-oxidation, metal chelation and free radical scavenging. Its good photothermal conversion ability has broad prospects in polymer composites, but the polar functional groups on the surface of eumelanin make it tend to aggregate in polymers. In the case of excessive eumelanin in the polymer, the electron transfer ability is given, which will reduce the insulation performance of the material. At present, reversible adhesives have not been prepared using eumelanin. Summary of the invention
[0004] In view of this, the present invention provides an epoxy resin adhesive and a preparation method and application thereof to solve the defects existing in the prior art.
[0005] In a first aspect, the present invention provides an epoxy resin adhesive, comprising the following raw materials: adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl;
[0006] Wherein, adhesive A comprises epoxy resin and barium titanate;
[0007] Adhesive B includes epoxy resin, eumelanin, and histidine.
[0008] Preferably, in the epoxy resin adhesive, the barium titanate is barium titanate surface-modified with a silane coupling agent.
[0009] Preferably, in the epoxy resin adhesive, the mass ratio of epoxy resin to barium titanate in adhesive A is (80-120):(10-30);
[0010] And / or, the mass ratio of epoxy resin, eumelanin and histidine in adhesive B is (80-120):(10-30):(3-7);
[0011] And / or, the mass ratio of adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl is (0-100):(10-100):(0-10):(5-15);
[0012] And / or, the epoxy resin is a liquid epoxy resin.
[0013] In a second aspect, the present invention further provides a method for preparing the epoxy resin adhesive, comprising the following steps:
[0014] Mixing epoxy resin and barium titanate to obtain adhesive A;
[0015] Mixing epoxy resin, eumelanin and histidine to obtain adhesive B;
[0016] Adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain an epoxy resin adhesive.
[0017] Preferably, in the preparation method of the epoxy resin adhesive, the barium titanate is barium titanate surface-modified with a silane coupling agent, and the modification method comprises the following steps:
[0018] adding a silane coupling agent to alcohol to obtain a mixed solution;
[0019] Add barium titanate into the mixed solution, stir, filter and dry to obtain barium titanate surface-modified with a silane coupling agent.
[0020] Preferably, in the method for preparing the epoxy resin adhesive, the alcohol comprises at least one of ethanol, methanol and glycerol.
[0021] Preferably, in the preparation method of the epoxy resin adhesive, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, 3-ureapropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane and 3-mercaptopropylmethyldiethoxysilane.
[0022] Preferably, in the preparation method of the epoxy resin adhesive, the mass ratio of the silane coupling agent, the alcohol, and the barium titanate is (1-3):(80-120):(15-25).
[0023] Preferably, in the method for preparing the epoxy resin adhesive, adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain the epoxy resin adhesive.
[0024] In a third aspect, the present invention also provides an application of the epoxy resin adhesive or the epoxy resin adhesive prepared by the preparation method in wood processing, artificial board materials, and electronic device packaging.
[0025] The present invention has the following beneficial effects compared with the prior art:
[0026] 1. The epoxy resin adhesive of the present invention comprises: adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl; wherein adhesive A comprises epoxy resin and barium titanate; adhesive B comprises epoxy resin, eumelanin and histidine; the epoxy resin adhesive of the present invention comprises perovskite (barium titanate) with a high dielectric constant and eumelanin with a good photothermal effect, and has excellent insulation and a high photothermal conversion rate; since the adhesive has a large number of reversible hydrogen bonds and ester bonds, the adhesive can be reused through photothermal reaction, and since the adhesive of the present invention has a large number of polar functional groups, it also has excellent adhesion to polar substrates such as metals, ceramics, glass, and wood;
[0027] 2. The preparation method of the epoxy resin adhesive of the present invention uses liquid epoxy resin as a raw material, based on reversible hydrogen bonds, ester bonds and true melanin with photothermal effect, through a simple ring-opening reaction, the amino group of histidine reacts with the epoxy group on the epoxy resin, and a large number of polar functional groups are introduced into the epoxy resin molecular chain to promote the dispersion of true melanin, so as to prepare an adhesive B with high photothermal conversion efficiency; in order to ensure the insulation of the adhesive during use, a perovskite (barium titanate) with a high dielectric constant is added, and a large number of hydroxyl groups are introduced into the surface of barium titanate through surface modification, which is helpful for its dispersion in the epoxy resin, and provides cross-linking points, enhances the mechanical properties of the material, and is filled into the epoxy resin to obtain an adhesive A; when used, the adhesive A and the adhesive B are mixed in a certain proportion, and then tannic acid and a curing agent 4,4-diaminobiphenyl are added to obtain a recyclable epoxy resin composite insulating adhesive based on the photothermal effect, which can be used for the bonding of glass plates and metal sheets, the assembly of circuit components, and the splicing of plastic models. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 It is the recycling efficiency of the epoxy resin adhesive prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0032] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials: adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl;
[0033] Wherein, adhesive A comprises epoxy resin and barium titanate;
[0034] Adhesive B includes epoxy resin, eumelanin, and histidine.
[0035] It should be noted that the epoxy resin adhesive of the present invention includes eumelanin, which is a two-molecule indole structure formed by oxidation of tyrosine, namely DHI (5,6-dihydroxyindole) and DHICA (5,6-dihydroxyindole acid). Specifically, the chemical structures of DHI (5,6-dihydroxyindole) and DHICA (5,6-dihydroxyindole acid) are as follows:
[0036]
[0037] The epoxy resin adhesive of the present invention has perovskite (barium titanate) with a high dielectric constant and true melanin with good photothermal effect, and has excellent insulation and a high photothermal conversion rate; since the adhesive has a large number of reversible hydrogen bonds and ester bonds, the adhesive can be reused through photothermal reaction. Since the adhesive of the present invention has a large number of polar functional groups, it also has excellent adhesion to polar substrates such as metal, ceramics, glass, and wood.
[0038] In some embodiments, the barium titanate is barium titanate surface-modified with a silane coupling agent.
[0039] In the above embodiment, the surface of barium titanate is modified by a silane coupling agent, which can introduce a large number of hydroxyl groups into the surface of barium titanate, which helps its dispersion in the epoxy resin, provides cross-linking points, and enhances the mechanical properties of the material.
[0040] In some embodiments, the mass ratio of epoxy resin to barium titanate in adhesive A is (80-120):(10-30).
[0041] In some embodiments, the mass ratio of epoxy resin and barium titanate surface-modified with a silane coupling agent in adhesive A is (80-120):(10-30).
[0042] In some embodiments, the mass ratio of epoxy resin, eumelanin, and histidine in adhesive B is (80-120):(10-30):(3-7).
[0043] In some embodiments, the mass ratio of adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl is (0-100):(10-100):(0-10):(5-15). Preferably, the mass ratio of adhesive A, adhesive B and tannic acid is (100):(10-100):(1-10):10.
[0044] In some embodiments, the epoxy resin is a liquid epoxy resin. Specifically, the epoxy resin is liquid epoxy resin 828EL, which is an electronic grade, diluent-free and unmodified bisphenol A epoxy resin with good wettability and good filler anti-settling properties, small curing shrinkage, excellent bonding properties, and excellent electrical and mechanical properties.
[0045] Based on the same concept, the present invention also provides a method for preparing the above-mentioned epoxy resin adhesive, comprising the following steps:
[0046] S1, mixing epoxy resin and barium titanate to obtain adhesive A;
[0047] S2, mixing epoxy resin, eumelanin and histidine to obtain adhesive B;
[0048] S3. Adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain an epoxy resin adhesive.
[0049] In some embodiments, epoxy resin and barium titanate are mixed and subjected to vacuum degassing treatment to obtain adhesive A.
[0050] In some embodiments, epoxy resin, eumelanin, and histidine are mixed and subjected to vacuum degassing treatment to obtain adhesive B.
[0051] In some embodiments, the barium titanate is barium titanate surface-modified by a silane coupling agent, and the modification method comprises the following steps:
[0052] S1, adding a silane coupling agent to alcohol to obtain a mixed solution;
[0053] S2. Add barium titanate to the mixed solution, stir, filter, and dry to obtain barium titanate surface-modified with a silane coupling agent.
[0054] In some embodiments, the alcohol includes at least one of ethanol, methanol, and glycerol. Preferably, the alcohol is ethanol.
[0055] In some embodiments, the silane coupling agent includes at least one of γ-aminopropyl triethoxysilane, 3-ureapropyl trimethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl methyl diethoxysilane. Preferably, the silane coupling agent is γ-aminopropyl triethoxysilane (KH-550).
[0056] In some embodiments, the mass ratio of the silane coupling agent, alcohol, and barium titanate is (1-3):(40-60):(5-15). Preferably, the mass ratio of the silane coupling agent, alcohol, and barium titanate is 1:50:10.
[0057] In some embodiments, adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain an epoxy resin adhesive.
[0058] In some embodiments, in some embodiments, the barium titanate is barium titanate surface-modified with a silane coupling agent, and the modification method comprises the following steps:
[0059] S1, adding silane coupling agent to ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0060] S2. Add barium titanate to the mixed solution under stirring. After adding all the barium titanate particles, stir for 40 to 50 minutes to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact with the silane coupling agent molecules. Filter.
[0061] The obtained product is placed in a vacuum oven and dried at 60-70° C. for 4-6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0062] In some embodiments, adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain an epoxy resin adhesive with a high dielectric constant and high light-to-heat conversion efficiency.
[0063] The preparation method of the epoxy resin adhesive of the present invention uses liquid epoxy resin as a raw material, based on reversible hydrogen bonds, ester bonds and eumelanin with photothermal effect, through a simple ring-opening reaction, the amino group of histidine reacts with the epoxy group on the epoxy resin, a large number of polar functional groups are introduced into the epoxy resin molecular chain, and the dispersion of eumelanin is promoted to prepare an adhesive B with high photothermal conversion efficiency; in order to ensure the insulation of the adhesive during use, perovskite (barium titanate) with a high dielectric constant is added, and a large number of hydroxyl groups are introduced into the surface of barium titanate through surface modification, which is helpful for its dispersion in the epoxy resin, provides cross-linking points, enhances the mechanical properties of the material, and is filled into the epoxy resin to obtain the adhesive A; when in use, the adhesive A and the adhesive B are open-chain mixed in a double-roll mill in a certain ratio, and then tannic acid and 4,4-diaminobiphenyl are added to obtain a recyclable epoxy resin composite insulating adhesive based on the photothermal effect, which can be applied to the bonding of glass plates and metal sheets, the assembly of circuit devices, and the splicing of plastic models.
[0064] Specifically, the mechanism of dispersing eumelanin of the present invention is as follows:
[0065]
[0066] Histidine reacts with epoxy groups through addition reaction, and the grafted polymer chain segments have hydroxyl, amino and carboxyl groups. These polar groups form a large number of hydrogen bonds with eumelanin, which promotes its uniform dispersion in the material.
[0067] The mechanism of dispersing barium titanate in the present invention is that the silane coupling agent performs surface modification by forming weak hydrogen bonds with adsorbed oxygen on the surface of barium titanate, so that the silane coupling agent is coated on the surface of barium titanate and a large number of hydroxyl groups are exposed to form a large number of hydrogen bonds with epoxy rubber.
[0068] The epoxy resin adhesive of the present invention can be reused many times. The mechanism is that the product is rich in a large number of reversible hydrogen bonds and amide bonds, which can be regenerated under heating conditions. True melanin has good photothermal conversion efficiency, and reversible bonds can also be regenerated through illumination. Once a traditional adhesive is bonded to a material, it cannot be reversibly reused. When the bonded material is a detachable device, multiple disassembly and reorganization will cause the adhesive to be used multiple times, which is neither convenient nor environmentally friendly. In the present invention, due to the presence of reversible hydrogen bonds and ester bonds, it can be reused many times under illumination conditions. The photothermal conversion filler used in the present invention is natural and cheap true melanin. Compared with traditional photothermal conversion fillers, true melanin is abundant in supply, simple to process, and has a lower production cost. The preparation method of the present invention is simple, the reaction time is short, and the required reaction device is simple. Therefore, the method of the present invention is easy to promote, has low time cost, low energy consumption, and is expected to be industrialized.
[0069] The epoxy resin adhesive and preparation method of the present application are further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. If not specifically stated, the technical means adopted in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0070] In the following examples, eumelanin is obtained by centrifugal separation of cuttlefish ink sacs. For the specific method, refer to the authorized patent: CN112625462B - A method for extracting melanin from cuttlefish ink.
[0071] Example 1
[0072] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 90 parts of adhesive A, 10 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4,4-diaminobiphenyl;
[0073] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0074] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0075] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0076] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0077] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0078] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0079] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0080] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0081] S3. At room temperature, 90 parts by weight of adhesive A, 10 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0082] Example 2
[0083] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 80 parts of adhesive A, 20 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0084] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0085] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0086] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0087] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0088] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0089] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0090] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0091] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0092] S3. At room temperature, 80 parts by weight of adhesive A, 20 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0093] Example 3
[0094] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 70 parts of adhesive A, 30 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0095] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0096] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0097] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0098] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0099] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0100] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0101] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0102] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0103] S3. At room temperature, 70 parts by weight of adhesive A, 30 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0104] Example 4
[0105] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 60 parts of adhesive A, 40 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0106] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0107] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0108] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0109] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0110] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0111] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0112] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0113] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0114] S3. At room temperature, 60 parts by weight of adhesive A, 40 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0115] Example 5
[0116] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 50 parts of adhesive A, 50 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0117] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0118] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0119] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0120] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0121] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0122] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0123] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0124] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0125] S3. At room temperature, 50 parts by weight of adhesive A, 50 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0126] Example 6
[0127] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 40 parts of adhesive A, 60 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0128] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0129] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0130] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0131] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0132] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0133] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0134] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0135] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0136] S3. At room temperature, 40 parts by weight of adhesive A, 60 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0137] Example 7
[0138] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 30 parts of adhesive A, 70 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0139] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0140] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0141] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0142] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0143] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0144] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0145] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0146] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0147] S3. At room temperature, 30 parts by weight of adhesive A, 70 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0148] Example 8
[0149] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 20 parts of adhesive A, 80 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0150] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0151] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0152] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0153] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0154] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0155] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0156] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0157] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0158] S3. At room temperature, 20 parts by weight of adhesive A, 80 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0159] Example 9
[0160] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 10 parts of adhesive A, 90 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0161] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0162] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0163] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0164] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0165] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0166] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0167] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0168] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0169] S3. At room temperature, 10 parts by weight of adhesive A, 90 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4,4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0170] Example 10
[0171] The embodiment of the present application provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 100 parts of adhesive B, 5 parts of tannic acid and 10 parts by weight of 4-4 diaminobiphenyl;
[0172] Wherein, adhesive B comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, and the epoxy resin is liquid epoxy resin 828EL;
[0173] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0174] S1, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0175] S2. At room temperature, 100 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0176] Comparative Example 1
[0177] This comparative example provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 60 parts of adhesive A, 40 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0178] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin and 20 parts of barium titanate; the epoxy resin is liquid epoxy resin 828EL;
[0179] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0180] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0181] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate are stirred and mixed, and vacuum degassing is performed to obtain adhesive A;
[0182] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0183] S3. At room temperature, 60 parts by weight of adhesive A, 40 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0184] Comparative Example 2
[0185] This comparative example provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 60 parts of adhesive A, 40 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0186] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0187] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of true melanin, the epoxy resin is liquid epoxy resin 828EL;
[0188] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0189] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0190] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0191] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0192] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0193] S2, 100 parts by weight of epoxy resin and 20 parts by weight of true melanin are stirred and mixed, and vacuum degassing is performed to obtain adhesive B;
[0194] S3. At room temperature, 60 parts by weight of adhesive A, 40 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0195] Comparative Example 3
[0196] This comparative example provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 60 parts of adhesive A, 40 parts of adhesive B, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0197] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 2 parts of silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)), and the epoxy resin is liquid epoxy resin 828EL;
[0198] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL.
[0199] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0200] S1, 100 parts by weight of epoxy resin and 2 parts by weight of silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) are stirred and mixed, and vacuum degassing is performed to obtain adhesive A;
[0201] S2, 100 parts by weight of epoxy resin and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain adhesive B;
[0202] S3. At room temperature, 60 parts by weight of adhesive A, 40 parts by weight of adhesive B, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0203] Comparative Example 4
[0204] This comparative example provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 60 parts of adhesive A, 40 parts of adhesive B and 10 parts by weight of 4-4 diaminobiphenyl;
[0205] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0206] Adhesive B includes the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of eumelanin, and 5 parts of histidine, wherein the epoxy resin is liquid epoxy resin 828EL;
[0207] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0208] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0209] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0210] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0211] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0212] S2, 100 parts by weight of epoxy resin, 20 parts by weight of eumelanin, and 5 parts by weight of histidine are stirred and mixed, and vacuum degassing is performed to obtain an adhesive B;
[0213] S3. At room temperature, 60 parts by weight of adhesive A, 40 parts by weight of adhesive B and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0214] Comparative Example 5
[0215] This comparative example provides an epoxy resin adhesive, comprising the following raw materials in parts by weight: 100 parts of adhesive A, 5 parts of tannic acid and 10 parts of 4-4 diaminobiphenyl;
[0216] Wherein, adhesive A comprises the following raw materials in parts by weight: 100 parts of epoxy resin, 20 parts of barium titanate surface-modified with a silane coupling agent; the epoxy resin is liquid epoxy resin 828EL;
[0217] The barium titanate surface modified by a silane coupling agent, wherein the modification method comprises the following steps:
[0218] S1, adding 2 parts by weight of a silane coupling agent (specifically γ-aminopropyltriethoxysilane (KH-550)) to 100 parts by weight of ethanol and mixing for 15 minutes to form a uniform solution to obtain a mixed solution;
[0219] S2. Add 20 parts by weight of barium titanate to the mixed solution under stirring, and stir for 45 minutes after adding all the barium titanate particles to prevent the barium titanate particles from precipitating and to allow the barium titanate to fully contact the silane coupling agent molecules. Filter the obtained product, and place it in a vacuum oven at 70° C. and dry it for 6 hours to obtain barium titanate surface-modified with a silane coupling agent.
[0220] The preparation method of the above-mentioned epoxy resin adhesive comprises the following steps:
[0221] S1, 100 parts by weight of epoxy resin and 20 parts by weight of barium titanate surface-modified with a silane coupling agent are stirred and mixed, and vacuum degassing is performed to obtain an adhesive A;
[0222] S2. At room temperature, 100 parts by weight of adhesive A, 5 parts by weight of tannic acid and 10 parts by weight of 4-4-diaminobiphenyl are mixed to obtain a reusable epoxy resin insulating adhesive based on photothermal conversion.
[0223] Performance Testing
[0224] Examples 1 to 10 and Comparative Examples 1 to 5 were poured into a rectangular mold and dried at 80° C. to form a film. The test method for the light-to-heat conversion efficiency coefficient of the prepared epoxy resin adhesive film is as follows:
[0225] A test system based on Lasever near-infrared laser (808 nm) irradiation, a test cell containing the epoxy resin adhesive film to be tested, and a HIKMICRO thermal imager were used to monitor the temperature. The photothermal conversion efficiency was calculated using the following formulas (1) to (6).
[0226]
[0227] (1)Q s =Qloss =hsΔT max =hs(T max -T surr ) (2)
[0228]
[0229]
[0230]
[0231]
[0232] Among them, η pt is the photothermal efficiency, h is the heat transfer coefficient, Q s Q is the photothermal energy input to the sample by near-infrared laser irradiation. loss is the heat energy lost to the surrounding environment, T max is the maximum value of the system temperature, T surr is the ambient temperature, I is the incident laser power (diameter ~1.2 cm, output power: 1.389 W, power density: ~1.2 W / cm -2 ), δ is the transmittance of glass (test tube) at 808nm (90%), A808 is the absorbance of the sample at 808nm, θ is the dimensionless driving force temperature, T is the system temperature, τ s is the sample system duration, m i C pi is the mass and heat capacity of the system components (deionized water: m1 = 2.52 g, C p1 =4.18Jg -1 K -1 ; Cuvette: m2 = 4.88 g, C p2 =0.879Jg -1 K -1 ; Test material: m3 = 0.1g, C p3 =1.96Jg -1 K -1 ), η * is the total light-to-heat conversion efficiency. When the laser is turned off, Qs = 0. The test results are shown in Table 1.
[0233] Table 1 - Photothermal conversion efficiency coefficients of epoxy resin adhesive films in Examples 1 to 10 and Comparative Examples 1 to 5
[0234]
[0235]
[0236] It can be seen from Table 1 that the addition of eumelanin rapidly improves the light-to-heat conversion efficiency of the adhesive, but when eumelanin is added continuously, the improvement of its light-to-heat conversion efficiency is not obvious. It can also be seen from the comparison between Comparative Example 2 and Example 4 that the dispersibility of eumelanin seriously affects its light-to-heat conversion performance.
[0237] The samples of Examples 1 to 10 and Comparative Examples 1 to 5 were poured into a rectangular mold and dried at 80° C. to form a film. The dielectric constant and dielectric loss of the prepared epoxy resin adhesive film were tested as follows:
[0238] The dielectric constant and dielectric loss of the material were tested using a Keysight E489 dielectric constant analyzer, and the dielectric constant and dielectric loss of the adhesive were tested in the frequency range of 10 Hz to 1 MHz. The test results are shown in Tables 2 and 3.
[0239] Table 2 - Dielectric constants of epoxy resin adhesive films in Examples 1 to 10 and Comparative Examples 1 to 5
[0240]
[0241]
[0242] Table 3 - Dielectric loss of epoxy resin adhesives in Examples 1 to 10 and Comparative Examples 1 to 5
[0243] Example 10Hz 1kHz 1MHz Example 1 0.054 0.025 0.318 Example 2 0.056 0.025 0.303 Example 3 0.058 0.025 0.307 Example 4 0.061 0.026 0.302 Example 5 0.063 0.026 0.307 Example 6 0.067 0.026 0.317 Example 7 0.069 0.026 0.311 Example 8 0.071 0.026 0.305 Example 9 0.073 0.026 0.307 Example 10 0.153 0.027 0.310 Comparative Example 1 0.075 0.026 0.312 Comparative Example 2 0.057 0.025 0.309 Comparative Example 3 0.149 0.027 0.310 Comparative Example 4 0.056 0.027 0.307 Comparative Example 5 0.052 0.025 0.302
[0244] The dielectric constants of barium titanate and melanin are both greater than that of epoxy resin. Among them, barium titanate has a larger dielectric constant, so as the amount of adhesive A with barium titanate added increases, the dielectric constant of epoxy resin adhesive increases and the dielectric loss decreases. The surface-modified barium titanate has better dispersibility and exhibits better dielectric properties, while the adhesive without barium titanate exhibits worse dielectric properties.
[0245] Examples 1 to 10 and comparative examples 1 to 5 were poured into a rectangular mold and dried at 80° C. to form a film. The mechanical properties of the prepared epoxy resin adhesive film were tested as follows: the tensile strength and elongation at break of the adhesive were tested using a universal tester;
[0246] The sample (i.e., the epoxy resin adhesive to be tested) has a size of 60×10 mm (length×width), the initial test distance between the two fixtures is 20 mm, and the sample is tested at a loading speed of 5 mm / min. The test results are shown in Table 4.
[0247] Table 4 - Mechanical properties of epoxy resin adhesive films in Examples 1 to 10 and Comparative Examples 1 to 5
[0248] Example Tensile strength(MPa) Elongation at break (%) Example 1 50.86 9.23 Example 2 49.25 12.87 Example 3 48.17 13.22 Example 4 47.45 13.89 Example 5 45.21 14.12 Example 6 42.82 14.45 Example 7 41.24 14.72 Example 8 40.52 14.88 Example 9 39.15 14.92 Example 10 38.88 15.01 Comparative Example 1 32.08 7.85 Comparative Example 2 31.57 7.36 Comparative Example 3 30.22 8.03 Comparative Example 4 24.33 8.10 Comparative Example 5 52.68 8.56
[0249] As can be seen from Table 4, since adhesive A has more hydrogen bond interactions than adhesive B, when in use, adhesive A mainly plays the role of increasing tensile strength. The polymer in adhesive B has a side group with large steric hindrance, which is conducive to the movement of the molecular chain and plays the role of increasing deformation when in use. With the increase of adhesive B, the tensile strength decreases slightly, while the elongation at break increases slightly. Since the dispersibility of the filler (barium titanate and true melanin) plays a decisive role in the mechanical properties of the material, the agglomerated filler causes the material to be unevenly stressed, so the mechanical strength of comparative examples 1 and 2 without good dispersion decreases rapidly. Tannic acid has a large number of hydroxyl functional groups, which can provide more cross-linking sites in the material, so comparative example 4, which does not add tannic acid for cross-linking, shows lower mechanical properties.
[0250] The bonding strength test method of the epoxy resin adhesives prepared in Examples 1 to 10 and Comparative Examples 1 to 5 is as follows:
[0251] The epoxy resin adhesives prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were evenly pasted on round bars of 304 stainless steel (50 mm long × 15 mm in diameter), polypropylene (50 mm long × 15 mm in diameter), and polytetrafluoroethylene (50 mm long × 15 mm in diameter), and baked at 80° C. for 30 minutes. The resulting adhesive bars were then clamped on an iron frame, a 1 kg weight was hung, and the stickiness was tested, and the hanging time was recorded, as shown in Table 5.
[0252] Table 5 - Adhesion performance of epoxy resin adhesives in Examples 1 to 10 and Comparative Examples 1 to 5
[0253]
[0254]
[0255]
[0256] As can be seen from Table 5, all adhesives have better adhesion to 304 stainless steel. The presence of fillers increases the interaction force within the material, hinders the molecular chain movement of the epoxy resin, and improves the adhesion. The larger the filler volume fraction, the stronger the resistance and the higher the adhesion. When the large particle size accounts for 60% or more of the total volume mass, the viscosity of the adhesive decreases because the small particle size is filled between the large particles and acts as a ball bearing. When the filler is not evenly dispersed, the particle size increases. Although it hinders the movement of the molecular chain, it makes the force in the material uneven, and finally shows a decrease in adhesion.
[0257] The shear strength of the epoxy resin adhesives prepared in Examples 1 to 10 and Comparative Examples 1 to 5 is determined as follows:
[0258] The epoxy resin adhesives in Examples 1 to 10 and Comparative Examples 1 to 5 were pasted on 304 stainless steel, polypropylene and polytetrafluoroethylene, and the thickness of the adhesive layer was controlled to be 0.2 mm. The other side of the substrate was taken out and fixed to it, and the overlap size was 20 mm × 25 mm, and baked at 80°C for 30 minutes. The shear strength test was carried out using a tensile machine with a tensile rate of 5 mm / min. The shear strength was obtained, as shown in Table 6.
[0259] Table 6 - Shear strength of epoxy resin adhesives in Examples 1 to 10 and Comparative Examples 1 to 5
[0260]
[0261]
[0262]
[0263] It can be seen from Table 6 that all adhesives have greater shear strength for 304 stainless steel. The shear strength increases slightly with the increase of component B and reaches the maximum in Practical Example 4.
[0264] The cyclic bonding test method of the adhesive is as follows:
[0265] The epoxy resin adhesive prepared in Example 4 was pasted on 304 stainless steel, polypropylene and polytetrafluoroethylene respectively, and the thickness of the adhesive layer was controlled to be 0.2mm. Take out the other side of the substrate and fix it with it. The overlap size is 20mm×25mm, and bake at 80°C for 30 minutes. Use a stretching machine to test the shear strength at a stretching rate of 5mm / min. Get the shear strength. Irradiate the bonding sample of the damaged adhesive under near-infrared light for 2 hours, overlap again, and the overlap size is consistent with the above. Irradiate under near-infrared light for 2 hours and apply a pressure of 0.4MPa. After natural cooling, use a stretching machine to test the shear strength at a stretching rate of 5mm / min. Get the shear strength. Repeat the above process twice again. As shown in Table 7. The following formula is used to calculate the recycling efficiency:
[0266] E = δ / δ0;
[0267] Wherein, E is the recycling efficiency, δ0 is the initial tensile strength, and δ is the tensile strength after the cycle. The recycling efficiency of the epoxy resin adhesive prepared in Example 4 is as follows: Figure 1 shown.
[0268] The shear strength of the epoxy resin adhesive prepared in Example 4 after three cycles of bonding is shown in Table 7 below.
[0269] Table 7 - Shear strength of epoxy resin adhesive under three cycles of bonding in Example 4
[0270]
[0271] It can be seen from Table 7 that before the first two cycles, the bonding ability of the epoxy resin adhesive in Example 4 to the material did not change significantly, indicating that it has good reversible bonding ability.
[0272] from Figure 1 It can be seen that when the epoxy resin adhesive of the present invention is cycled once, the recycling efficiency on the 304 stainless steel substrate is 85%, the recycling efficiency on the polypropylene substrate is 83%, and the recycling efficiency on the polytetrafluoroethylene substrate is 77%; when the cycle number is 2, the recycling efficiency of the three can be maintained at 76%, 73% and 74% respectively; but when the cycle number reaches 3 times, the utilization efficiency drops to 44%, 43% and 40% respectively.
[0273] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An epoxy resin adhesive, characterized in that: The invention comprises the following raw materials: adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl; Wherein, adhesive A comprises epoxy resin and barium titanate; Adhesive B includes epoxy resin, eumelanin, and histidine.
2. The epoxy resin adhesive according to claim 1, characterized in that The barium titanate is barium titanate surface-modified with a silane coupling agent.
3. The epoxy resin adhesive according to any one of claims 1 to 2, characterized in that: The mass ratio of epoxy resin and barium titanate in adhesive A is (80-120):(10-30); And / or, the mass ratio of epoxy resin, eumelanin and histidine in adhesive B is (80-120):(10-30):(3-7); And / or, the mass ratio of adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl is (0-100):(10-100):(0-10):(5-15); And / or, the epoxy resin is a liquid epoxy resin.
4. A method for preparing the epoxy resin adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing epoxy resin and barium titanate to obtain adhesive A; Mixing epoxy resin, eumelanin and histidine to obtain adhesive B; Adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain an epoxy resin adhesive.
5. The method for preparing the epoxy resin adhesive according to claim 4, characterized in that: The barium titanate is barium titanate surface-modified with a silane coupling agent, and the modification method comprises the following steps: adding a silane coupling agent to alcohol to obtain a mixed solution; Add barium titanate into the mixed solution, stir, filter and dry to obtain barium titanate surface-modified with a silane coupling agent.
6. The method for preparing the epoxy resin adhesive according to claim 4, characterized in that: The alcohol includes at least one of ethanol, methanol and glycerol.
7. The method for preparing the epoxy resin adhesive according to claim 4, characterized in that: The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, 3-ureapropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane and 3-mercaptopropylmethyldiethoxysilane.
8. The method for preparing the epoxy resin adhesive according to claim 4, characterized in that: The mass ratio of silane coupling agent, alcohol and barium titanate is (1-3):(40-60):(5-15).
9. The method for preparing the epoxy resin adhesive according to claim 4, characterized in that: Adhesive A, adhesive B, tannic acid and 4,4-diaminobiphenyl are mixed to obtain an epoxy resin adhesive.
10. Use of the epoxy resin adhesive according to any one of claims 1 to 3 or the epoxy resin adhesive prepared by the preparation method according to any one of claims 4 to 9 in wood processing, artificial board materials, and electronic device packaging.
